GAMBARAN KARIES GIGI SERTA KEBIASAAN MAKAN MAKANAN KARIOGENIK PADA SISWA SDN 5 ABIANSEMAL TAHUN 2018 - I Nyoman Wirata; Ni Wayan Arini; Ni Nyoman Dewi Supariani; Kadek Diantini (Jurnal Kesehatan Gigi (Dental Health Journal), 2021)
School-aged children are one of the most vulnerable groups of caries, because they generally have lack of knowledge and behavior about oral health, such as the habit of consuming cariogenic foods that trigger the dental caries. The purpose of this research is to know the caries description and the habit of consuming cariogenic food in students of SDN 5 Abiansemal in 2018. The technique used in this research is descriptive technique with the number of respondents 44 students. The result of the research on 44 students of SDN 5 Abiansemal shows the average of caries permanent teeth in students of SDN 5 Abiansemal is 1,61. The permanent caries mode of teeth is the tooth 46 ( teeth first permanent mandibular molar of the right lower). The frequency of students who have the habit of consuming most cariogenic foods is moderate category (2 times a day) that is 52, 3%. The frequency of students with caries teeth based on the dietary habits of cariogenic foods isfrom 7 students who have the habit of eating cariogenic foods high ( 3 times a day) as many as 7 students(100%) had caries teeth with an average dental caries 3,42 means that one student experiences three to four caries teeth. These results suggest that students who consume high-categorical cariogenic foods tend to experience more dental caries.